Perancangan Sistem Informasi Manajemen Lelang Kendaraan Berbasis Web - Dharmawan, Dicky (PT. Lentera Ilmu Publisher, 2023)
Auction services at PT Hino Finance Indonesia during the COVID-19 pandemic experienced obstacles such as government regulations prohibiting activities that could have an impact on auction services that were less than optimal for auction participants. Each auction participant was asked to implement their activities by paying attention to the principles of physical distancing. To answer this problem, a Web-based Vehicle Auction management information system was produced to manage auction data, which consists of five certificates, all of which are online-based and can be accessed by auction participants and auction admins at any time. The system development method used is the prototype method and is continued with the data collection process through the stages of observation, interviews, and literature study. In developing this system, the author used the PHP and MYSQL programming languages for processing the database server. The results of this study state that this application is the best solution to overcome problems regarding the auction process for auction participants during the COVID-19 pandemic, in order to achieve an effective and efficient activity in supporting vehicle auction activities at PT Hino Finance Indonesia.